Pembatalan Nikah karena Pemalsuan Identitas dan Poligami: (Studi Kasus Putusan PA Banjarmasin No. 1079/Pdt.G/2025/PA.Bjm) - Nur Adila Nasution; Muhammad Jetrin Alvito; Davin Ade Putra Pratama; Muhamad Alvin Najmi (Indo Publishing, 2025)
This study seeks to understand the considerations of judges in the Religious Court when deciding to annul a marriage due to false identity claims. The analysis focuses on the principles of Islamic law that form the basis of such decisions. In legal terms, annulment means that the marriage is deemed never to have existed. As a result, the legal status of the parties and the management of joint property are affected. The study employs a normative juridical method by examining relevant cases and legal provisions. Data were collected through a literature review, encompassing primary, secondary, and tertiary legal sources. The findings highlight the importance of understanding and complying with marital regulations, particularly regarding polygamy, to ensure the protection of individual rights. Judges also refer to other statutory provisions on marriage. Since the marriage was deemed invalid, it was annulled, which terminated the marital relationship and voided the official marriage documents. Nevertheless, children born from such a marriage remain legally recognized as legitimate and retain inheritance rights from their parents.